Inadvertent obstacle contacts when older adults step over obstacles: Effect of sex, self-reported fatigue, gait parameters, and prescription medications - Becker, Timothy; Rietdyk, Shirley (Brazilian journal of motor behavior, 2022)
Background: Tripping is a common cause of falls, but the factors that are associated with trip risk are understudied. Aim: To quantify inadvertent trips with a stationary, visible obstacle in older adults, and to determine how inadvertent trips are related to fatigue, sex, gait measures, and prescription medications. Methods: Forty-one subjects walked on a 6 m walkway and stepped over a visible, stationary obstacle (height: 25% of leg length) 100 times; inadvertent trips with the obstacle were documented. We also collected gait measures on a clear walkway, self-reported fatigue every 25 obstacle crossing trials, and number of prescription medications. Participants were categorized as: 0 contacts or ≥1 contact. Results: The obstacle was contacted by 15 participants (37%) in 29 trials (0.7% of all trials); 52% of contacts were with the lead limb. Self-reported fatigue increased during the obstacle crossing protocol (p<0.001). Participants in the ≥1 contact group had slower gait speed, shorter stride length, and higher gait cycle time variability (p≤0.041). They also reported higher maximum fatigue (p=0.022) and a higher number of prescription medications (p=0.019). Males and females were not different in contact frequency (p=0.93). Interpretation: Inadvertent trips were not uncommon in older adults, even with a visible, stationary obstacle. Lead limb contacts indicate that older adults will have more difficulty recovering their balance after a trip. The strong association between fatigue (induced by walking) and impaired gait is highly relevant when quantifying gait in older adults, and also when developing fall prevention programs.